English-learning stress and performance in Chinese college students: A serial mediation model of academic anxiety and academic burnout and the protective effect of grit - Xu, Liling; Wang, Zhenhai; Tao, Zhiyuan; Yu, Chengfu (Frontiers in Psychology, 2022)
Having to adapt to a new environment with various other challenges while completing their studies, Chinese college students experience intense stress related to the study of the English language. However, there has been little research on the serial mediating mechanism of English-learning stress on academic English performance. We constructed a moderated serial mediation model to test the effect of academic anxiety and academic burnout and explored whether grit can block the decrease in academic performance caused by English-learning stress. Results show that: (1) both academic anxiety and academic burnout mediate the relationship between English-learning stress and performance; (2) academic anxiety and academic burnout show a significant serial mediating role between academic pressure and academic English performance; and (3) grit significantly moderates the relationship between academic burnout and academic English performance. These results lead us to believe that cultivating the grit of Chinese college students may be an effective way to improve the academic performance of those experiencing high English-learning stress.